Optimization of the experimental parameters of fluticasone propionate microparticles for pulmonary delivery using a box behenken design - P V Patel; T G Soni; V T Thakkar; T R Gandhi (Wolters Kluwer Medknow Publications, 2012)
The objective of this study was to examine extensively the influences of formulation and process variables on the microparticles. The microparticles were generated by the spray-drying technique using polymer chitosan, mannitol along with L-leucine. The effects of various experimental parameters such as polymer concentration, inlet temperature, and feed flow rate on particle size and production yields were evaluated by means of experimental box-behnken design. Multiple regression analysis was carried out and response surfaces were obtained. Optimized formulation and check points batches were selected by feasibility and grid search. Experimental design it was evaluated that inlet temperature and polymer concentration influence on the production yield. Feed flow rate impact on particle size. Results showed that spray drying technique yield 985 to 4060 nm indicate micro size range and production yield was found in between 27.01-52.96%. The selection of appropriate parameters yielded spray-dried microparticles characterized by narrow dimensional distribution. In our present work, prepared microparticles using the spray-drying technique and systematically estimated their feasibility for the pulmonary delivery of microparticles by careful investigations of their characteristics and aerosolization properties. Spray drying technique yield optimum size for deposition beyond the narrow airway into the alveoli and suitable for respiratory deposition.